Social class and changing families in an unequal America - Carlson, Marcia J.; England, Paula (Studies in social inequality., 2011)
American families are far more diverse and complex today than they were 50 years ago. As ideas about marriage, divorce, and remarriage have changed, so too have our understandings about cohabitation, childbearing, parenting, and the transition to adulthood. Americans of all socioeconomic backgrounds have witnessed changes in the nature of family life, but as this book reveals, these changes play out in very different ways for the wealthy or well off than they do for the poor.